Labor factors influencing the working environment of the nursing staff at the “Carlos Alberto Seguín Escobedo” National Hospital - Uturunco Vera, Milagros Lizbeth (2018)
Objectives: To establish the labor factors influencing the working environment of the nurses working at the “Carlos Alberto Seguin Escobedo” (CASE) National Hospital, Arequipa. Material and Methods: It is a field study, relational and cross-sectional. The population was composed of 214 nurses. The instruments were questions form work climate and organizational climate scale (EDCO). Results: The labor factors that occur frequently in the Hospital nursing staff (CASE) are the motivation in the company, the nurses claim a 51.0% never recognize and reward their work, 84.0% consider that the institution does not provide Labor stability, 81.0% rarely cares about their training. The Labor factor economic motivation, 45.0% consider that the salary they perceive is inadequate, the economic incentives received from the institution are infrequent 62.0%. As for the environmental Labor factor, 49.0% consider the relationship with their superiors is good, 63.0% the relationship with their partners is Good. The work environment factor, 55.0% Consider the physical environment unfavorable and 88.0% consider the institution provide them with the resources necessary to carry out their activities only sometimes. Conclusions: the labor factors of greatest influence in the working environment of the Hospital nurses (CASE), are: The recognition they receive from their institution for the work well done, job stability, relations with the superiors and with the Co-workers.